Perception Analysis of Green Construction Implementation on Construction Projects For Contractors in Banda Aceh City - Anita Rauzana; Nurul Hidayati Binti Saidan; Wira Dharma (Elkawnie: Journal of Islamic Science and Technology, 2021)
Abstract: Along with the increasing use of natural resources, and the large number of construction waste dumping in the environment, environmental damage is increasingly visible. Many areas, especially Banda Aceh City, have experienced land and air degradation due to the pattern of life and the number of people. Currently, the construction project has a new concept, namely green construction, which is believed to be able to improve the environment caused by various developments by reducing the occurrence of environmental damage. The research objective was to analyze the perception of the application of green construction in construction projects in the city of Banda Aceh in determining the most dominant factors and the relationship between the factors of implementing green construction (X) on costs (Y). The research location was in the city of Banda Aceh. Secondary data, namely contractor company data. Primary data were 34 questionnaires. The results of data analysis using SPSS include a validity test, reliability test, frequency analysis, and Pearson product-moment correlation test. Based on the research results, it was found that the most dominant green construction factor was the application of energy conservation in construction (X5) of 95.1%, the application of energy conservation (X10) of 92.8%, and the use of construction materials (X8) of 92.5%. The largest correlation coefficient value was obtained in energy conservation (X10) of 0.882.Abstrak: Seiring meningkatnya pemakaian sumber daya alam dan banyaknya pembuangan limbah konstruksi di lingkungan, kerusakan lingkungan semakin terlihat. Telah banyak daerah-daerah khususnya Kota Banda Aceh mengalami degradasi lahan dan udara karena pola hidup dan jumlah manusia. Saat ini proyek konstruksi mempunyai sebuah konsep baru yaitu green construction yang dipercaya mampu memperbaiki lingkungan yang diakibatkan oleh berbagai pembangunan dengan mereduksi terjadinya kerusakan lingkungan. Tujuan penelitian untuk menganalisis persepsi penerapan green construction pada proyek konstruksi di Kota Banda Aceh dalam menentukan faktor-faktor yang paling dominan dan hubungan antara faktor-faktor penerapan green construction (X) terhadap biaya (Y). Lokasi penelitian di Kota Banda Aceh. Data sekunder yaitu data perusahaan kontraktor. Data primer sebanyak 34 kuesioner. Hasil analisis data menggunakan SPSS meliputi uji validitas, uji reliabilitas, analisis frekuensi, dan uji korelasi pearson product moment. Berdasarkan hasil penelitian, diperoleh bahwa faktor green construction  yang paling dominan adalah penerapan konservasi energi pada pelaksanaan konstruksi (X5) sebesar 95,1%, penerapan konservasi energi (X10) sebesar 92,8%, dan penggunaan material konstruksi (X8) sebesar 92,5%. Nilai koefisien korelasi terbesar didapat pada konservasi energi (X10) sebesar 0,882.